1999
DOI: 10.1590/s0100-879x1999000400003
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in parasites and parasite-induced apoptosis in the host immune system: a new approach to parasitic diseases

Abstract: Apoptosis, a form of programmed cell death (PCD), has been described as essential for normal organogenesis and tissue development, as well as for the proper function of cell-renewal systems in adult organisms. Apoptosis is also pivotal in the pathogenesis of several different diseases. In this paper we discuss, from two different points of view, the role of apoptosis in parasitic diseases. The description of apoptotic death in three different species of heteroxenic trypanosomatids is reviewed, and consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 42 publications
1
32
0
1
Order By: Relevance
“…As Leishmania parasites are transferred by the sandfly, apoptosis-like cell death could serve to restrict population growth in the vector, hereby increasing the life span of the vector and increasing the transmission rate, as shown for other protozoan parasites. 3,4 From another point of view it is also tempted to speculate that the presence of apoptotic-like parasites has an immune-silencing effect, as has been shown upon apoptotic cell clearance during homeostasis. Santos et al already showed that phosphatidylserine exposure by Toxoplasma gondii is fundamental for granting survival of the parasite in murine macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Leishmania parasites are transferred by the sandfly, apoptosis-like cell death could serve to restrict population growth in the vector, hereby increasing the life span of the vector and increasing the transmission rate, as shown for other protozoan parasites. 3,4 From another point of view it is also tempted to speculate that the presence of apoptotic-like parasites has an immune-silencing effect, as has been shown upon apoptotic cell clearance during homeostasis. Santos et al already showed that phosphatidylserine exposure by Toxoplasma gondii is fundamental for granting survival of the parasite in murine macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…As most protozoan parasites are vector transmitted, it may be necessary to restrict the population size in the vector, as shown for Trypanosoma brucei and Plasmodium. 3,4 From an overall population perspective, the induction of apoptosis could also be employed by the parasites to evade early immune responses. Evidence supporting the idea that apoptosis contributes to survival of the overall population was given by the fact that phagocytosis of apoptotic-like parasites induces production of anti-inflammatory mediators, likely to silence phagocytes enabling the intracellular survival of viable parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Cell death of lymphocytes is necessary to preserve a healthy and balanced immune system [35]. Nevertheless, if during an infectious process lymphocyte apoptosis occurs prior to pathogen elimination, it could restrict the magnitude of the effector response [36], especially if the apoptosis occurs at early stages of lymphocyte development. Thus, immature B cell reduction during an infection would limit antibody production and favor parasite replication and chronicity; so the identification of the mechanisms ruling lymphocyte apoptosis represents a current and major challenge in biomedical research.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon plays an important role in the immunopathogenesis of several parasitic diseases (27,28). Studies on cell death in protozoonoses have also focused on its possible role in the immunopathology of experimental Chagas disease (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%